Replicated flux measurements of 1, 3-dichloropropene emissions from a bare soil under field conditions. (October 2018) - Ashworth, Daniel J.; Yates, Scott R.; Anderson, Ray G.; van Wesenbeeck, Ian J.; Sangster, Jodi; Ma, Li
Abstract: Field experiments offer the most acceptable approach to quantifying agricultural fumigant emissions but there is an absence of replicated field data in reported literature. Air concentration profiles of 1, 3-dichloropropene (1, 3-D) were determined on duplicate masts above the center of a treated field over 14 days. Meteorological parameters were also measured. Three meteorological approaches were then used to determine the total and flux density emissions of 1, 3-D. Across the three calculation methods, the averages of the duplicated measurements showed total emission losses of cis 1, 3-D ranging from 27% to 36% and of trans 1, 3-D ranging from 18% to 24%. The replicate measurements differed by between 1.6 and 7.7 percentage points, which we consider to be excellent replicability. Flux densities over time showed maximum emissions during the first nighttime and early morning of the day following application. A general declining trend in emission fluxes was accompanied by nighttime peaks. Flux density curves during the experiment showed excellent agreement between replicates, with linear regression of the two data sets yielding r 2 values of 0.95–0.98 and slopes of 1.01–1.17. To our knowledge, this is the first time that replicated fumigant fluxes have been reported. The high degree of replicability indicates the robustness of the approaches and lends credence to previous non-replicated flux data. Highlights: There is an absence of replicated field fumigant flux measurements in the literature. Replicated 1, 3-dichloropropene fluxes were determined using meteorological methods. Replicate total emissions differed by just 1.6 to 7.7 percentage points. Flux densities showed very good agreement between replicates (r 2 = 0.95 to 0.98). The high degree of replicability lends credence to previous non-replicated flux data.